2015
DOI: 10.1111/jop.12340
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of lip cancer occurrence over the 1990–2011 period in public hospitals in Madrid, Spain

Abstract: The pattern of lip cancer reported to Public Hospitals of Madrid is changing: declining rates are noted since 2001-02. However, it is necessary to monitor these data to confirm the observed trends in future years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 59 publications
7
11
0
1
Order By: Relevance
“…The mean age of the patients was 65 years, similar to previous studies (dos Santos et al , ; Batista et al , ; Domínguez‐Gordillo et al , ; Pastuszek et al , ). In addition, lip SCC more commonly affects men (dos Santos et al , ; Vartanian et al , ; Batista et al , ; Salihu et al , ; Domínguez‐Gordillo et al , ; Pastuszek et al , ) and white patients (dos Santos et al , ; Batista et al , ). The fact that men work outdoors more frequently than women and are often subject to unprotected sun exposure probably explains the male predominance of this cancer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The mean age of the patients was 65 years, similar to previous studies (dos Santos et al , ; Batista et al , ; Domínguez‐Gordillo et al , ; Pastuszek et al , ). In addition, lip SCC more commonly affects men (dos Santos et al , ; Vartanian et al , ; Batista et al , ; Salihu et al , ; Domínguez‐Gordillo et al , ; Pastuszek et al , ) and white patients (dos Santos et al , ; Batista et al , ). The fact that men work outdoors more frequently than women and are often subject to unprotected sun exposure probably explains the male predominance of this cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Chronic exposure to UVB radiation can produce harmful effects such as skin (Lucas et al , ) and lip cancer (Batista et al , ). Lip SCC accounts for 95% of all malignant neoplasms in the lower lip (Domínguez‐Gordillo et al , ). The vermilion border of the lower lip is the preferred site involved (dos Santos et al , ; Batista et al , ; Moretti et al , ; Domínguez‐Gordillo et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies of lip cancer, especially for LSCC, have been reported in the United States , Canada , Finland , Italy , Japan , Turkey , Serbia , Mexico , Germany , and Spain , especially focusing on the clinicopathology and treatment modality. Some articles focused on outcome analysis , local recurrence, regional recurrence , distant metastasis , and prognostic factors .…”
Section: Discussionmentioning
confidence: 99%
“…Some articles focused on outcome analysis , local recurrence, regional recurrence , distant metastasis , and prognostic factors . Epidemiological data of LBCC have been reported in Mexico , Italy , Canada , the United States , and Spain .…”
Section: Discussionmentioning
confidence: 99%